Kajian Kriminologi Terhadap Upaya Penanganan Kasus Kekerasan Dalam Rumah Tangga (KDRT) Di Indonesia - Merung, Prisilla Viviane (Veritas et Justitia, 2016)
AbstractDomestic violence had been and is still underreported.  Inhibiting factor is the widely held perception that outside intervention in cases of domestic violence is unwelcome and asking outside help will bring shame to the family. It is and should be treated by family members among themselves. To make matter worse, there is the general tendency to shift the blame to the victim. This article discusses domestic violence, especially those directed against women, from the legal (normative) as well as criminological perspective.  It is telling that after its recognition as a special crime by virtue of the Penal Code (in general terms) and by Law no. 23 of 2004 re. abolition of domestic violence, the public perception shifted for the better. Consequently, more and more victims of domestic violence, with the support of their families, report their case to the police.